2015
DOI: 10.1016/j.molonc.2015.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated interleukin‐6 expression contributes to erlotinib resistance in head and neck squamous cell carcinoma

Abstract: Despite the role of epidermal growth factor receptor (EGFR) signaling in head and neck squamous cell carcinoma (HNSCC) development and progression, clinical trials involving EGFR tyrosine kinase inhibitors (TKIs) have yielded poor results in HNSCC patients. Mechanisms of acquired resistance to the EGFR TKI erlotinib was investigated by developing erlotinib-resistant HNSCC cell lines and comparing their gene expression profiles with their parental erlotinib-sensitive HNSCC cell lines using microarray analyses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 21 publications
(29 reference statements)
0
40
0
Order By: Relevance
“…The development and characterization of these ER-HNSCC cells have been previously described [22] and the raw gene expression data has been reported previously [GEO accession #GSE62061]. Combined enrichment analysis of all 4 ER-HNSCC cells compared to their respective ES counterparts revealed that the majority of the top ten deregulated Gene Ontology (GO) processes associated with ER-HNSCC cells are related to stress or stimulus responses (Figure 1A).…”
Section: Resultsmentioning
confidence: 94%
“…The development and characterization of these ER-HNSCC cells have been previously described [22] and the raw gene expression data has been reported previously [GEO accession #GSE62061]. Combined enrichment analysis of all 4 ER-HNSCC cells compared to their respective ES counterparts revealed that the majority of the top ten deregulated Gene Ontology (GO) processes associated with ER-HNSCC cells are related to stress or stimulus responses (Figure 1A).…”
Section: Resultsmentioning
confidence: 94%
“…[26][27][28] An increased autocrine stimulation of the IL-6/STAT3 pathway could unleash the cells from their dependency on EGFR. 27) Notably, increased levels of IL-6 was reported in around 30% of NSCLC patients and in EGFR-TKI treated cell culture.…”
Section: Discussionmentioning
confidence: 99%
“…42) Inhibiting IL-6/STAT3 pathway suppressed cancer cell proliferation and restored the sensitivity to TKI. 26,43) This suggests that the antagonism of IL-6/STAT3 pathway could be therapeutically beneficial for the treatment of drug-resistant tumors that are driven by EMT-like phenomena. 44) In this study, we observed the activation of IL-6/STAT3 signaling pathway in ER cells, elevated IL-6 promotes EMT through altered expression of N-cadherin, vimentin and E-cadherin leading to enhanced cancer invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This receptor complex then regulates the Janus kinase-signal transducer and activator of transcription 3 (STAT3) pathway, as well as other signaling pathways [21, 22]. Activation of the IL-6/STAT3 pathway has been shown to result into a range of tumor-promoting effects, including (a) stimulation of cancer cell proliferation via direct control of cell cycle-associated proteins [23]; (b) activation of tumor cell survival pathways that could contribute to resistance to anti-cancer therapeutics [24]; (c) induction of tumor EMT which, as indicated below, could facilitate tumor migration and invasiveness and enhance metastatic dissemination; and (d) modulation of infiltrating immune cells by directly affecting the differentiation of myeloid cells [25]. Attesting to the tumor-promoting effect of this inflammatory cytokine, high levels of serum IL-6 have been associated with poor patient clinical outcome [26] and with resistance to therapies [27] in various tumor types.…”
Section: Tumor-driven Inflammation: Key Soluble Immune-mediatorsmentioning
confidence: 99%